Mandibular advancement device design: A systematic review on outcomes in obstructive sleep apnea treatment. (December 2021) - Venema, Julia A.M. Uniken; Rosenmöller, Boudewijn R.A.M.; de Vries, Nico; de Lange, Jan; Aarab, Ghizlane; Lobbezoo, Frank; Hoekema, Aarnoud
Summary: Obstructive Sleep Apnea (OSA) is often treated with Mandibular Advancement Devices (MADs). It is unclear whether particular design features are superior to others in terms of OSA alleviation. In order to facilitate clinical decision-making, this systematic review summarizes the objective and subjective outcomes of different available MAD designs. Studies comparing different MAD designs in OSA treatment were searched. After screening 1887 titles and abstracts, 20 original RCTs and six cohort studies were included. 14 articles were systematically reviewed in a meta-analysis. The decrease in AHI was significantly different between some of the MAD designs. The clinical relevance of the observed differences was however limited. Monoblock appliances performed more favorable, compared to bilateral thrust (effect size:-0.37; CI:-1.81 to 0.07). Midline traction appliances performed more favorable, compared to other designs. Custom appliances performed more favorable, compared to thermoplastic appliances (effect size:0.86; CI:-0.62 to 2.35). Furthermore, there were no clinically relevant differences between MAD designs in reduction of ESS, compliance, preference, side effects, and cost effectiveness. With respect to the included trials, presently there is not one superior custom MAD design in OSA treatment regarding the effect on AHI reduction, ESS improvement, compliance, preference, side effects, cost effectiveness, and other disease-related outcomes. We confirm custom MAD designs perform superior to thermoplastic MAD designs.